The Prevalence of Hepatitis B Surface Antigen (HBsAg) and its Influencing Factors in Pregnant Women Referring to Healthcare Centers of Dehloran, Iran in 2011-2012 - Leila Kheiri; Somayeh Makvandi (Mashhad University of Medical Sciences, 2015)
Background & aim: Hepatitis B virus (HBV) infection is a major global health concern. According to the statistics, the prevalence of this infection is moderate in Iran. Pregnant mothers, who are infected with the virus (virus carriers), can transmit the infection to their fetus. This study aimed to determine the prevalence of hepatitis B surface antigen (HBsAg) and its influencing factors in pregnant women, referring to healthcare centers of Dehloran, Iran. Methods:In this descriptive, cross-sectional study, the sample consisted of all pregnant women with medical records, referring to healthcare centers of Dehloran city for prenatal care during 2011-2012. Census sampling was applied and subjects' medical records were reviewed. Demographic and pregnancy-related data, and HBV test results were recorded. For data analysis, descriptive statistics, t-test and Fisher's exact test were applied, using SPSS version 16.0. P-value < 0.05 was considered statistically significant. Results: In this study, the medical records of 850 pregnant women were studied. The prevalence of positive HBsAg test results was 0.59% in the study population. Positive HBsAg was significantly correlated with parity (P=0.003) and abortion (P=0.04). However, there was no significant association between HBsAg results and other variables such as age (P=0.16), mother's educational level (P=0.16), spouse's educational level (P=0.66), place of residence (P=0.66), history of cesarean section (P=0.18), work experience at healthcare centers (P=1.0), blood transfusion (P=1.0) or HBV infection in the first-degree relatives (P=1.0). Conclusion: Although the prevalence of positive HBsAg was relatively low among pregnant women in Dehloran city, HBV screening during pregnancy is highly recommended.